Determinasi Akuntabilitas Pengelolaan Keuangan Daerah: (studi kasus pada pemerintah kota palopo) - Amanda Amanda; Halim Usman; Andika Rusli (Pusat Riset dan Inovasi Nasional, 2025)
Accountability in regional financial management is a crucial element in realizing transparent, effective, and responsible governance. This study aims to examine the extent to which public participation and internal supervision affect accountability in regional financial management. This study uses a quantitative method involving 80 respondents consisting of people who have been involved in development planning discussions and government officials within the Palopo City Government. Data were obtained through questionnaires and analyzed using a statistical approach. The results of the analysis show that both public participation and internal supervision have a positive and significant influence on accountability in regional financial management. This finding confirms that increasing public participation and strengthening internal supervision mechanisms play an important role in building more accountable regional financial management.